2017
DOI: 10.1177/0897190017690641
|View full text |Cite
|
Sign up to set email alerts
|

ACE Inhibitor-Induced Angioedema of the Small Bowel: A Case Report and Review of the Literature

Abstract: Angiotensin-converting enzyme (ACE) inhibitors are known to cause angioedema. Most ACE inhibitor-induced angioedema cases describe swelling in the periorbital region, tongue, and pharynx. We describe a case of a 62-year-old female with presumed angioedema of the small bowel after more than a 2-year history of lisinopril use (with no recent changes in her dose of 40 mg orally twice daily). The patient presented with nausea and intermittent left middle and upper quadrant abdominal pain and denied history of angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…In a review by Wilin et al , that included 25 unique cases, authors found similar findings as those mentioned previously, in addition, 52% (13/25) of cases included patients who presented on several different occasions, prior to obtaining an official diagnosis, likely secondary to decreased knowledge and awareness of ACEi-induced visceral angioedema 7. Interestingly, 42% (8/19) of patients presented within 1 week of initiation of an ACEi and 32% (6/19) presented at or after 1 year of ACEi initiation 7. In this review, the longest period an individual was on ACEi therapy prior to onset of visceral angioedema was 9 years 7.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In a review by Wilin et al , that included 25 unique cases, authors found similar findings as those mentioned previously, in addition, 52% (13/25) of cases included patients who presented on several different occasions, prior to obtaining an official diagnosis, likely secondary to decreased knowledge and awareness of ACEi-induced visceral angioedema 7. Interestingly, 42% (8/19) of patients presented within 1 week of initiation of an ACEi and 32% (6/19) presented at or after 1 year of ACEi initiation 7. In this review, the longest period an individual was on ACEi therapy prior to onset of visceral angioedema was 9 years 7.…”
Section: Discussionsupporting
confidence: 69%
“…In a review by Scheirey et al that included 20 patients, authors also found a high proportion of obese individuals (65%) 6. In a review by Wilin et al , that included 25 unique cases, authors found similar findings as those mentioned previously, in addition, 52% (13/25) of cases included patients who presented on several different occasions, prior to obtaining an official diagnosis, likely secondary to decreased knowledge and awareness of ACEi-induced visceral angioedema 7. Interestingly, 42% (8/19) of patients presented within 1 week of initiation of an ACEi and 32% (6/19) presented at or after 1 year of ACEi initiation 7.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations